Interface sulfur-resistant optical silicone composition for LED lamp beads
Patent Information
- Application Number
- CN202611146492.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-27
AI Technical Summary
[0027]1、本发明通过控制三烯丙基异氰脲酸酯与三烷氧基硅烷的部分硅氢加成程度,使所得反应产物同时具有能够参与主体硅胶固化的残余烯丙基和能够与支架界面发生作用的三烷氧基硅基;相对于将两种原料直接物理混合的方式,部分硅氢加成反应产物能够以更稳定的形式引入透明有机硅固化网络,有利于减少界面改性组分在固化及老化过程中的迁移。
Smart Images

Figure CN122978719A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organosilicon optical packaging materials technology, specifically to an interface sulfur-resistant optical silicone composition for LED chips. Background Technology
[0002] LED chips typically consist of a bracket, an LED chip mounted within the bracket, and a transparent encapsulation material covering the LED chip. To improve the bracket's reflectivity to visible light, some LED chip brackets have a silver-plated metallic surface, and the bracket cup is formed using materials such as polyphthalamide, poly(1,4-cyclohexanediol) terephthalate, or epoxy molding compound. Addition-type organopolysiloxane compositions possess advantages such as good optical transparency, high heat resistance, fewer curing byproducts, and relatively low curing shrinkage, making them suitable for encapsulating LED chips and other optoelectronic semiconductor components.
[0003] US8741994B2 discloses a class of organopolysiloxane compositions for optical semiconductor devices. This composition utilizes an alkenyl-containing organopolysiloxane, a hydrogen-containing organopolysiloxane, and a hydrosilylation catalyst to form a curing network. By selecting appropriate organosilicon components, the curing performance, adhesion, and device reliability of the optical semiconductor packaging material are improved. This technical approach demonstrates that addition-type organosilicon materials can meet the requirements of optical semiconductor packaging through the combination of alkenyl-containing components, hydrogen-containing components, and reactive auxiliary components.
[0004] CN102604449A discloses a type of addition-curing silicone resin composition and a photonic semiconductor device package formed using the composition. This technology improves the transparency, mechanical properties, heat resistance, and encapsulation reliability of the cured product by selecting and combining silicone resins, alkenyl-containing organopolysiloxanes, hydrogen-containing crosslinking components, and hydrosilylation catalysts. This document reflects a technical direction of improving the performance of photonic semiconductor packaging by adjusting the structure and crosslinking network of silicone resins.
[0005] The aforementioned prior art provides an addition-curable transparent silicone material for optical semiconductor devices. However, the reliability of LED beads in sulfur-containing environments is not only related to the composition and cross-linking state of the transparent package body, but may also be affected by the interface state between the transparent package body, the silver-plated metal surface, and the support cup.
[0006] When using a thickening component with multiple reactive groups, if the component has too low reactivity with the host network, it may migrate in the cured product or precipitate from the interface region; if its reactivity with the host network is too high, it may be fixed before reaching or acting on the scaffold interface, making it difficult to fully exert the interface anchoring effect.
[0007] Furthermore, introducing components with high polarity or high alkoxy content may affect the compatibility, viscosity, storage stability, curing speed, hygroscopicity, light transmittance, and haze of the composition. Therefore, the structure, reactivity, and amount of the interface-modifying components need to be matched with the optical silicone matrix system.
[0008] Based on the above, it is necessary to provide a reactive component that can participate in the curing of the main silicone and can also interact with the interface of the scaffold. The ratio between co-curable groups and interfacial interaction groups in the reactive component should be controlled to achieve a balance between optical transparency, network fixation ability, interfacial adhesion retention ability and reliability in sulfur-containing environments. Summary of the Invention
[0009] The purpose of this invention is to provide an interface sulfur-resistant optical silicone composition for LED chips, which improves the interfacial bonding between the transparent silicone encapsulator and the silver-plated metal surface and the support cup while maintaining addition curing ability and optical transparency, and reduces the migration of sulfur-containing substances along the corresponding adjacent interfaces.
[0010] To achieve the above objectives, the present invention adopts the following technical solution:
[0011] This invention provides an interface sulfur-blocking optical silicone composition for LED lamp beads, comprising, by weight: 100 parts of an alkenyl polyorganosiloxane, wherein each molecule of the alkenyl polyorganosiloxane contains at least two alkenyl groups bonded to silicon atoms; an organohydrogen polysiloxane, wherein the amount of the organohydrogen polysiloxane is such that the molar ratio of hydrogen groups bonded to silicon atoms to all alkenyl groups capable of participating in hydrosilylation is 0.85~1.30; a platinum group metal catalyst, wherein the content of platinum element relative to the total mass of the composition is 1 / 2 to 25 parts per million; 0.30~1.80 parts of a portion of the hydrosilylation reaction product; and 0.01~0.30 parts of a hydrosilylation reaction inhibitor.
[0012] The partial hydrosilylation reaction product is obtained by partial hydrosilylation reaction of triallyl isocyanurate with at least one trialkoxysilane selected from trimethoxysilane and triethoxysilane, wherein the molar ratio of the hydrogen group bonded to the silicon atom in the trialkoxysilane to the allyl group in the triallyl isocyanurate is 0.25~0.45.
[0013] The partial hydrosilylation reaction product contains an isocyanurate ring, residual allyl and trialkoxysilyl groups, with the residual alkenyl content being 3.0~6.5 mmol / g, the alkoxy content being 5.0~9.0 mmol / g, and the residual hydrogen group content bonded to silicon atoms being ≤0.20 mmol / g.
[0014] Furthermore, the alkenyl polyorganosiloxane includes one or more of terminal vinyl polydimethylsiloxane, terminal vinyl methyl phenyl polysiloxane, and vinyl-containing silicone resin; the alkenyl content of the alkenyl polyorganosiloxane is 0.15~1.50 mmol / g, and the viscosity at 25°C is 1000~40000 mPa·s.
[0015] Furthermore, the organohydrogen polysiloxane includes one or two of terminal hydrogen polydimethylsiloxane and methylhydrosiloxane-dimethylsiloxane copolymer; the organohydrogen polysiloxane has a hydrogen group content bonded to silicon atoms of 1.0~10.0 mmol / g, and an average of 3~15 hydrogen groups bonded to silicon atoms per molecule.
[0016] Furthermore, the partially hydrosilylation reaction product is obtained by partially hydrosilylation reaction of triallyl isocyanurate and triethoxysilane; the viscosity of the partially hydrosilylation reaction product at 25°C is 50~3000 mPa·s, and the water content is not higher than 1000 parts per million.
[0017] Furthermore, the 100 parts of alkenyl polyorganosiloxane include 60-90 parts of vinyl-terminated polydimethylsiloxane and 10-40 parts of vinyl-containing silicone resin; the molar ratio of monofunctional siloxane structural units to tetrafunctional siloxane structural units in the vinyl-containing silicone resin is 0.6-1.2, and the vinyl content is 0.2-1.5 mmol / g.
[0018] The present invention also provides a method for preparing the above-mentioned interface sulfur-resistant optical silicone composition for LED beads, comprising the following steps:
[0019] With a molar ratio of 0.25 to 0.45 of hydrogen groups bonded to silicon atoms in triallyl isocyanurate to allyl groups in triallyl isocyanurate, the triallyl silane is added to a reaction system containing triallyl isocyanurate and a platinum group metal catalyst over 60 to 180 minutes, and the reaction is carried out at 55 to 75°C for 2 to 6 hours until the content of residual hydrogen groups bonded to silicon atoms in the reaction system is not higher than 0.20 mmol / g.
[0020] The reactants were treated at 50-85°C and 2-20 kPa for 0.5-3 hours and filtered using a filter medium with a pore size of 0.2-2.0 micrometers to obtain the partial hydrosilylation reaction product.
[0021] The aforementioned hydrosilylation reaction product is mixed with 5% to 25% of the total mass of alkenyl polyorganosiloxane at 20 to 50°C for 20 to 90 minutes to prepare an interfacial sulfur-inhibiting masterbatch.
[0022] The interface sulfur barrier masterbatch is sequentially mixed with the remaining alkenyl polyorganosiloxane, hydrosilylation inhibitor and organohydrogen polysiloxane, and a platinum group metal catalyst is added at ≤35°C. The mixture is then degassed for 5 to 40 minutes at an absolute pressure of 0.5 to 15 kPa to obtain the interface sulfur barrier optical silicone composition for LED beads.
[0023] Furthermore, it is applied to the preparation of transparent LED bead packages with silver-plated supports, so that the cured composition comes into contact with the silver-plated metal surface and the support cup, and continuously covers the adjacent interface between the silver-plated metal surface and the support cup.
[0024] The present invention also provides the application of the above-mentioned interface sulfur-resistant optical silicone composition for LED beads, wherein the composition is applied to a silver-plated bracket on which the LED chip is mounted, so that the composition covers the LED chip and the interface between the silver-plated metal surface and the bracket cup; after application, it is left to stand at 20~50°C for 5~30 minutes, then pre-cured at 70~100°C for 15~50 minutes, and then post-cured at 120~155°C for 30~120 minutes.
[0025] The present invention also provides an LED lamp bead, including a bracket, an LED chip disposed within the bracket, and a transparent silicone encapsulation covering the LED chip. The bracket includes a silver-plated metal surface and a bracket cup formed of polyphthalamide, poly(1,4-cyclohexanedimethyl terephthalate), or epoxy molding compound. The transparent silicone encapsulation is formed by curing an interface sulfur-resistant optical silicone composition for LED lamp beads and continuously covers the silver-plated metal surface and the adjacent interface between the silver-plated metal surface and the bracket cup.
[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0027] 1. This invention controls the degree of partial hydrosilylation between triallyl isocyanurate and trialkoxysilane, so that the resulting reaction product simultaneously has residual allyl groups that can participate in the curing of the main silicone and trialkoxysilyl groups that can interact with the scaffold interface. Compared with the method of directly physically mixing the two raw materials, the partial hydrosilylation reaction product can be introduced into the transparent organosilicon curing network in a more stable form, which is beneficial to reduce the migration of interface modification components during curing and aging.
[0028] 2. The degree of hydrosilylation limited by this invention can achieve a balance between network fixation ability and interface anchoring ability; compared with the reaction product with too low degree of trialkoxysilyl introduction, the reaction product of this invention can provide more sufficient interfacial interaction; compared with the reaction product with too high degree of allyl consumption, the reaction product of this invention can retain more sufficient co-curing ability, thereby improving the interfacial adhesion retention state after sulfur aging.
[0029] 3. The present invention uses a partial hydrosilylation reaction product and a partial alkenyl polyorganosiloxane to pre-form a masterbatch, which is beneficial to improve the dispersion uniformity of the interface modification component in the main organosilicon system and reduce the impact of excessively high local concentration, phase separation or uneven curing on transparency and interface performance.
[0030] 4. By controlling the amount of hydrosilylation reaction products added, the present invention enables the composition to achieve interfacial sulfur inhibition while maintaining viscosity, curing hardness, visible light transmittance and low haze suitable for LED transparent packaging, thus avoiding the possible decline in optical performance caused by simply increasing polar interfacial modification components.
[0031] 5. The transparent silicone encapsulation formed by this invention continuously covers the silver-plated metal surface and the adjacent interface between the silver-plated metal surface and the support cup, which helps improve the interface continuity in sulfur-containing environments, reduces the degree of blackening in the silver-plated area, and slows down the decrease in LED luminous flux caused by changes in the reflectivity of the silver layer. Compared with conventional epoxy alkoxysilane adhesion-enhancing systems, the technical effects of this invention are not limited to improving initial bond strength, but also include improving the interfacial bond retention ability after damp heat aging and sulfur-containing aging, and reducing the impact of sulfur-containing substances migrating along the adjacent interface of the support.
[0032] 6. The composition of the present invention uses alkenyl polysiloxane, organohydrogen polysiloxane and platinum group metal catalyst to form an addition curing system. It does not require the release of a large number of small molecule byproducts to complete the curing of the main network, and is suitable for LED lamp beads with requirements for transparency, dimensional stability and packaging reliability. Attached Figure Description
[0033] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0034] Figure 1 This is a schematic diagram of the preparation process of some of the hydrosilylation reaction products of the present invention.
[0035] Figure 2This is a schematic diagram illustrating the principle of the partial hydrosilylation reaction between triallyl isocyanurate and triethoxysilane according to the present invention.
[0036] Figure 3 This is a schematic diagram of the structure of an LED bead packaged using the composition of the present invention.
[0037] in, Figure 2 This only indicates a reaction relationship in which some allyl groups undergo hydrosilylation and some allyl groups remain; it does not indicate that the resulting reaction product is a single, specific compound.
[0038] Reference numerals: 1. Indicates the support cup body; 2. Silver-plated metal surface; 3. LED chip; 4. Transparent silicone encapsulation; 5. Adjacent interface. Detailed Implementation
[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] The following mechanism of action is a reasonable explanation based on the reactant structure, curing reaction relationship, and interfacial interaction, and does not constitute a limitation on the scope of protection of this invention. The residual allyl groups in the partially hydrosilylation reaction products can participate in the hydrosilylation curing of the optical silicone matrix system, fixing at least a portion of the reaction products in the cured network and reducing the possibility of migration, precipitation, or loss of the interfacial modification components after curing. Trialkoxysilane groups can undergo hydrolysis, condensation, or other interfacial interactions in the presence of trace amounts of moisture or active sites on the scaffold surface, thereby improving the bonding between the transparent silicone encapsulant and the silver-plated metal surface, as well as the scaffold cup.
[0041] The isocyanurate ring has a relatively rigid ring structure, which may restrict the chain segment movement and free volume in the interface region. The presence of residual allyl, trialkoxysilyl and isocyanurate rings in the same part of the hydrosilylation reaction product is beneficial to the mutual coordination of main network fixation, scaffold interface anchoring and interface region densification.
[0042] When the molar ratio of hydrogen groups bonded to silicon atoms in trialkoxysilane to allyl groups in triallyl isocyanurate is low, the amount of trialkoxysilane groups introduced into the reaction product may be insufficient, and the interfacial interaction is limited. When the molar ratio is high, the allyl groups in triallyl isocyanurate are excessively consumed, the ability of the reaction product to participate in the curing of the main silicone may be reduced, and the compatibility, hygroscopicity, or optical properties may be affected due to the increased alkoxy content.
[0043] Figure 1 The steps of feeding triallyl isocyanurate, adding a platinum group metal catalyst, adding triethoxysilane dropwise, partial hydrosilylation reaction, vacuum treatment, and filtration are shown to illustrate the sequence of preparation of the partial hydrosilylation reaction product.
[0044] Figure 2 This illustrates the hydrosilylation reaction between a portion of the allyl group in triallyl isocyanurate and a hydrogen group bonded to a silicon atom in triethoxysilane, while retaining a portion of unreacted allyl groups. Since the resulting reaction product may contain components with varying degrees of substitution, Figure 2 This does not represent a single, definitive chemical structure, and schematic diagrams of the chemical structures of unreacted, monoaddition, diaddition, and triaddition reactants are provided.
[0045] Figure 3 The diagram shows a support cup 1, a silver-plated metal surface 2, an LED chip 3, and a transparent silicone encapsulation 4. The transparent silicone encapsulation 4 covers the LED chip 3 and continuously covers the silver-plated metal surface 2 and the adjacent interface 5.
[0046] The vinyl-terminated polydimethylsiloxane of this invention has a viscosity of 5000 mPa·s at 25°C and a vinyl content of 0.30 mmol / g; the molar ratio of monofunctional siloxane structural units to tetrafunctional siloxane structural units in the vinyl-containing silicone resin is 0.80, and the vinyl content is 0.50 mmol / g; the methylhydrosiloxane-dimethylsiloxane copolymer has a silicon-bonded hydrogen group content of 4.50 mmol / g, with an average of 5-10 silicon-bonded hydrogen groups per molecule; a platinum-vinylsiloxane complex is used as a hydrosilylation catalyst; 1-ethynyl-1-cyclohexanol is used as a hydrosilylation reaction inhibitor; the purity of triallyl isocyanurate is not less than 98.0%; and the purity of triethoxysilane is not less than 97.0%.
[0047] Example 1:
[0048] The preparation method of the interface sulfur-resistant optical silicone composition for LED lamp beads in this embodiment includes the following steps:
[0049] Add 100.00 g of triallyl isocyanurate to a dry reactor, and add platinum-vinylsiloxane complex under dry nitrogen protection, so that the content of platinum element relative to the total mass of reactants is 1 part per million;
[0050] The reaction system was heated to 60°C, and 69.20 g of triethoxysilane was added dropwise over 120 minutes to make the molar ratio of hydrogen groups bonded to silicon atoms to allyl groups 0.35. After the addition was completed, the reaction was carried out at 65°C for 4 hours.
[0051] The product was treated at 70℃ and an absolute pressure of 5-10 kPa for 1.5 hours and then filtered through a filter medium with a pore size of 0.45 microns to obtain a portion of the hydrosilylation reaction product.
[0052] Take 0.80 parts by weight of the reaction product and 8.00 parts by weight of vinyl-terminated polydimethylsiloxane and mix them at 35°C for 30 minutes. Then add 62.00 parts by weight of vinyl-terminated polydimethylsiloxane, 30.00 parts by weight of vinyl-containing silicone resin and 0.08 parts by weight of 1-ethynyl-1-cyclohexanol and mix them.
[0053] Add methylhydrosiloxane-dimethylsiloxane copolymer to make the molar ratio of hydrogen groups bonded to silicon atoms to all reactive alkenyl groups 1.05; lower the temperature to below 30°C and add platinum-vinylsiloxane complex to make the platinum content in the composition 1 part per 10 million; mix for 10 minutes and then degas for 15 minutes under an absolute pressure of 2-10 kPa to obtain an interface sulfur-resistant optical silicone composition for LED lamp beads.
[0054] After dispensing the LED beads with an interface sulfur-resistant optical silicone composition, let them stand at 25°C for 15 minutes, pre-cur at 85°C for 30 minutes, and then post-cur at 140°C for 60 minutes.
[0055] Example 2:
[0056] The method for preparing the interface sulfur-resistant optical silicone composition for LED beads in this embodiment is the same as that in Example 1, except that 65.20 g of triethoxysilane is added dropwise to make the molar ratio of hydrogen groups bonded to silicon atoms to allyl groups 0.33, and 1.00 parts by mass of the obtained hydrosilylation reaction product is added.
[0057] The reaction product was first prepared into a masterbatch with 10.00 parts by weight of vinyl-terminated polydimethylsiloxane, and then mixed with 60.00 parts by weight of vinyl-terminated polydimethylsiloxane and 30.00 parts by weight of vinyl-containing silicone resin; the remaining preparation, degassing and curing conditions were the same as in Example 1.
[0058] Example 3:
[0059] The method for preparing the interface sulfur-resistant optical silicone composition for LED lamp beads in this embodiment is the same as that in Example 1, except that 49.40 g of triethoxysilane is added dropwise to make the molar ratio of hydrogen groups bonded to silicon atoms to allyl groups 0.25, and 0.30 parts by mass of the obtained hydrosilylation reaction product is added.
[0060] The reaction product was first mixed with 3.00 parts by weight of vinyl-terminated polydimethylsiloxane to form a masterbatch, and then mixed with 67.00 parts by weight of vinyl-terminated polydimethylsiloxane and 30.00 parts by weight of vinyl-containing silicone resin; the remaining preparation, degassing and curing conditions were the same as in Example 1.
[0061] Example 4:
[0062] The preparation method of the interface sulfur-resistant optical silicone composition for LED lamp beads in this embodiment is to prepare the composition according to the method of Example 1, except that 89.00 g of triethoxysilane is added dropwise to make the molar ratio of hydrogen groups bonded to silicon atoms to allyl groups 0.45, and 1.80 parts by mass of the obtained partial hydrosilylation reaction product is added.
[0063] The reaction product was first prepared into a masterbatch with 18.00 parts by weight of vinyl-terminated polydimethylsiloxane, and then mixed with 52.00 parts by weight of vinyl-terminated polydimethylsiloxane and 30.00 parts by weight of vinyl-containing silicone resin; the remaining preparation, degassing and curing conditions were the same as in Example 1.
[0064] Comparative Example 1:
[0065] This comparative example does not involve a partial hydrosilylation reaction beforehand. Instead, 0.473 parts by mass of triallyl isocyanurate and 0.327 parts by mass of triethoxysilane are physically mixed to ensure that the total amount and relative proportion of the raw materials correspond to the partial hydrosilylation reaction product in Example 1.
[0066] The resulting physical mixture was used to prepare samples according to the masterbatch preparation, composition mixing, degassing and curing methods of Example 1.
[0067] Comparative Example 2:
[0068] This comparative example prepared the reaction product according to the method of Example 1, except that 19.80 g of triethoxysilane was added dropwise, so that the molar ratio of hydrogen groups bonded to silicon atoms to allyl groups was 0.10, and the amount of reaction product added was 0.80 parts by mass.
[0069] The preparation, degassing, and curing conditions for the remaining compositions were the same as in Example 1.
[0070] Comparative Example 3:
[0071] This comparative example prepared the reaction product according to the method of Example 1, except that 138.30 g of triethoxysilane was added dropwise, so that the molar ratio of hydrogen groups bonded to silicon atoms to allyl groups was 0.70, and the amount of reaction product added was 0.80 parts by mass.
[0072] The preparation, degassing, and curing conditions for the remaining compositions were the same as in Example 1.
[0073] Comparative Example 4:
[0074] In this comparative example, 0.80 parts by weight of γ-glycidyl etheroxypropyltrimethoxysilane were used to replace part of the hydrosilylation reaction product in Example 1.
[0075] The silane was mixed with 8.00 parts by weight of vinyl-terminated polydimethylsiloxane, and then mixed with 62.00 parts by weight of vinyl-terminated polydimethylsiloxane, 30.00 parts by weight of vinyl-containing silicone resin and 0.08 parts by weight of 1-ethynyl-1-cyclohexanol. The remaining preparation, degassing and curing conditions were the same as in Example 1.
[0076] Test example:
[0077] The residual alkenyl content was determined by the iodine value method: approximately 0.2 g of sample was weighed, dissolved in 20 mL of chloroform, and then 25.00 mL of 0.1 mol / L iodoacetic acid monochloride solution was added. The mixture was reacted in the dark for 30 minutes. A 10% potassium iodide aqueous solution was added, and the solution was titrated with a 0.1 mol / L sodium thiosulfate standard solution. A blank test was performed simultaneously, and the residual alkenyl content was calculated based on the volume difference of the standard solution consumed by the blank and the sample.
[0078] The alkoxy content was determined by hydrolysis-gas chromatography: approximately 0.5 g of sample was weighed, and a tetrahydrofuran solution containing n-propanol as an internal standard and a 0.1% hydrochloric acid aqueous solution were added. The sample was hydrolyzed in a closed system at 60 °C for 2 hours. The released ethanol was determined using a gas chromatograph with a flame ionization detector, and the alkoxy content was calculated based on the calibration curve.
[0079] The content of residual hydrogen groups bonded to silicon atoms was determined by the alkaline hydrogen release gas volumetric method: 0.5~1.0 g of sample was weighed, dissolved in toluene, and 20% potassium hydroxide ethanol solution was added at 25±1℃; the hydrogen gas released by the reaction was collected and converted to the volume under standard conditions, and the content of residual hydrogen groups bonded to silicon atoms was calculated accordingly.
[0080] Moisture content was determined using the Karl Fischer coulometric method, with each sample measured in triplicate.
[0081] The viscosity of the composition was determined according to GB / T 2794-2022, and the test temperature was 25.0±0.5℃.
[0082] The hardness of the cured material was determined according to GB / T 39693.4-2025 using a Shore A hardness tester with a sample thickness of 6.0±0.5 mm.
[0083] Transmittance and haze were determined according to GB / T 2410-2008. The sample thickness was 1.00±0.05 mm, and the transmittance and haze at 450 nm were recorded.
[0084] The initial interfacial shear strength was tested using a model joint formed by a silver-plated copper sheet and a polyphthalamide sheet: the bonding area had a diameter of 6.0 mm and a thickness of 0.50 mm. After curing, the samples were placed at 25±2℃ and 50±5% relative humidity for 24 hours, and shear tests were performed at a loading rate of 1 mm per minute.
[0085] The damp heat aging was carried out according to GB / T 2423.3-2016, with conditions of 85±2℃, relative humidity of 85±3%, and 168 hours. After 2 hours of recovery, the interfacial shear strength was tested and the retention rate was calculated.
[0086] The sulfidation evaluation of the LED lamp bead silver-plated bracket was conducted in accordance with GB / T 2423.20-2014. The hydrogen sulfide volume fraction was 10±2 cubic centimeters / cubic meter, the temperature was 25±2℃, the relative humidity was 75±5%, the exposure time was 96 hours, and the interface shear strength was tested after 2 hours of recovery.
[0087] The blackening area ratio of LED beads was calculated using a unified microscopic imaging and fixed threshold binarization method, with 20 LED beads tested in each group.
[0088] Luminous flux was measured using an integrating sphere and a spectroradiometer. The LED beads were driven by a constant current of 20 mA. The luminous flux maintenance rate was the ratio of the luminous flux after sulfur aging to the luminous flux before sulfur aging.
[0089] The specific test results are shown in the table below:
[0090] Group Viscosity at 25℃ / mPa·s Shore A hardness 450 nm transmittance / % Haze / % Initial interfacial shear strength / MPa Shear retention rate after wet heat / % Shear retention rate after sulfur aging / % Blackened area percentage / % Light flux maintenance rate / % Example 1 6280 48 92.7 0.55 2.15 88.0 86.0 5.8 96.3 Example 2 6520 49 92.4 0.62 2.30 91.0 90.0 3.9 97.1 Example 3 6010 47 93.0 0.48 1.75 78.0 75.0 12.8 92.5 Example 4 7810 51 91.2 1.35 2.40 84.0 82.0 6.7 95.5 Comparative Example 1 6150 48 92.8 0.58 1.58 62.0 55.0 29.5 84.6 Comparative Example 2 6320 48 93.0 0.51 1.35 59.0 50.0 34.2 81.9 Comparative Example 3 7240 49 90.5 1.72 1.72 68.0 61.0 25.8 87.2 Comparative Example 4 6190 48 92.2 0.70 2.05 74.0 70.0 19.6 90.1
[0091] Analysis of experimental results:
[0092] Example 1 and Comparative Example 1 used similar ratios of triallyl isocyanurate and triethoxysilane, but Comparative Example 1 did not undergo a pre-treatment partial hydrosilylation reaction. The hardness and transmittance of the two groups were similar, while Example 1 exhibited higher interfacial shear retention after sulfur aging, a lower proportion of blackened silver plating area, and higher light transmittance retention. This comparison indicates that the effect is not solely due to the simultaneous presence of triallyl isocyanurate and triethoxysilane, but is related to the pre-formation of partial hydrosilylation reaction products containing residual allyl and triethoxysilyl groups.
[0093] Example 2 demonstrates superior overall results in terms of interfacial shear retention, blackening area ratio, and luminous flux retention. These results support the appropriate control of the degree of partial hydrosilylation and the selection of corresponding amounts to coordinate the network immobilization effect of residual allyl groups and the interfacial effect of triethoxysilane groups.
[0094] Example 3 is at the lower end of the intended protection range. Its interface retention performance after sulfur aging is lower than that of Example 1 and Example 2, but it is still better than Comparative Example 2, which has a lower molar ratio. This comparison is used to support the requirement that the amount of trialkoxysilane introduced needs to reach the corresponding lower limit.
[0095] Example 4 falls at the high end of the intended protection range, exhibiting a high initial interfacial shear strength, but the viscosity of the composition and the haze of the cured product are increased. This result suggests that increasing the degree of reaction and the amount added may enhance interfacial interactions, but compatibility, processability, and optical properties must be considered.
[0096] Comparative Example 2, with its lower degree of triethoxysilane incorporation, exhibited lower initial interfacial shear strength and retention rate after aging, but also a higher proportion of blackened area. This result supports the conclusion that insufficient incorporation of triethoxysilane groups makes it difficult to form adequate interfacial interactions.
[0097] Comparative Example 3 showed a higher degree of allyl group consumption, exhibiting a trend of decreased light transmittance, increased haze, and reduced interface retention after sulfur-containing aging. This result supports the recommendation that the degree of partial hydrosilylation reaction should not be too high, and that sufficient allyl groups should be retained to participate in the curing of the host network.
[0098] Comparative Example 4 used a conventional epoxy alkoxysilane, whose initial interfacial shear strength was similar to that of the examples, but its interfacial shear retention rate after sulfur aging was lower, and its blackened area ratio was higher. This indicates that the technical effect is not limited to initial adhesion enhancement, but also manifests in interfacial retention and silver plating surface protection under sulfur-containing environments.
[0099] The hardness of the various embodiments and comparative examples is within a similar range, while the interfacial shear retention rate and the proportion of blackened area after sulfur aging show significant differences. Therefore, it can be preliminarily ruled out that the sulfur-inhibiting effect is solely caused by the increase in the overall hardness of the cured product.
[0100] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
[0101] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. An interface sulfur-resistant optical silicone composition for LED lamp beads, characterized in that, By weight, it includes: 100 parts of an alkenyl polyorganosiloxane, wherein each molecule of the alkenyl polyorganosiloxane contains at least two alkenyl groups bonded to silicon atoms; an organohydrogen polysiloxane, wherein the amount of the organohydrogen polysiloxane is such that the molar ratio of hydrogen groups bonded to silicon atoms to all alkenyl groups capable of participating in the hydrosilylation reaction in the composition is 0.85 to 1.30; a platinum group metal catalyst, wherein the content of platinum element relative to the total mass of the composition is 1 / 2 to 25 parts per million; 0.30 to 1.80 parts of a portion of the hydrosilylation reaction product; and 0.01 to 0.30 parts of a hydrosilylation reaction inhibitor. The partial hydrosilylation reaction product is obtained by partial hydrosilylation reaction of triallyl isocyanurate with at least one trialkoxysilane selected from trimethoxysilane and triethoxysilane, wherein the molar ratio of the hydrogen group bonded to the silicon atom in the trialkoxysilane to the allyl group in the triallyl isocyanurate is 0.25~0.
45. The partial hydrosilylation reaction product contains an isocyanurate ring, residual allyl and trialkoxysilyl groups, with the residual alkenyl content being 3.0~6.5 mmol / g, the alkoxy content being 5.0~9.0 mmol / g, and the residual hydrogen group content bonded to silicon atoms being ≤0.20 mmol / g.
2. The interface sulfur-resistant optical silicone composition for LED beads according to claim 1, characterized in that, The alkenyl polyorganosiloxane includes one or more of terminal vinyl polydimethylsiloxane, terminal vinyl methyl phenyl polysiloxane, and vinyl-containing silicone resin; the alkenyl content of the alkenyl polyorganosiloxane is 0.15~1.50 mmol / g, and the viscosity at 25°C is 1000~40000 mPa·s.
3. The interface sulfur-resistant optical silicone composition for LED beads according to claim 1, characterized in that, The organohydrogen polysiloxane includes one or two of terminal hydrogen polydimethylsiloxane and methylhydrosiloxane-dimethylsiloxane copolymer; the organohydrogen polysiloxane has a hydrogen content of 1.0~10.0 mmol / g bonded to silicon atoms, and an average of 3~15 hydrogen groups bonded to silicon atoms per molecule.
4. The interface sulfur-resistant optical silicone composition for LED beads according to claim 1, characterized in that, The partial hydrosilylation reaction product is obtained by partial hydrosilylation reaction of triallyl isocyanurate with triethoxysilane; the viscosity of the partial hydrosilylation reaction product at 25°C is 50~3000 mPa·s.
5. The interface sulfur-resistant optical silicone composition for LED lamp beads according to claim 1, characterized in that, The 100 parts of alkenyl polyorganosiloxane include 60-90 parts of vinyl-terminated polydimethylsiloxane and 10-40 parts of vinyl-containing silicone resin; the molar ratio of monofunctional siloxane structural units to tetrafunctional siloxane structural units in the vinyl-containing silicone resin is 0.6-1.2, and the vinyl content is 0.2-1.5 mmol / g.
6. The method for preparing the interface sulfur-resistant optical silicone composition for LED lamp beads according to any one of claims 1 to 5, characterized in that, Includes the following steps: With a molar ratio of 0.25 to 0.45 of hydrogen groups bonded to silicon atoms in triallyl isocyanurate to allyl groups in triallyl isocyanurate, the triallyl silane is added to a reaction system containing triallyl isocyanurate and a platinum group metal catalyst over 60 to 180 minutes, and the reaction is carried out at 55 to 75°C for 2 to 6 hours until the content of residual hydrogen groups bonded to silicon atoms in the reaction system is not higher than 0.20 mmol / g. The reactants were treated at 50-85°C and 2-20 kPa for 0.5-3 hours and filtered using a filter medium with a pore size of 0.2-2.0 micrometers to obtain the partial hydrosilylation reaction product. The aforementioned hydrosilylation reaction product is mixed with 5% to 25% of the total mass of alkenyl polyorganosiloxane at 20 to 50°C for 20 to 90 minutes to prepare an interfacial sulfur-inhibiting masterbatch. The interface sulfur barrier masterbatch is sequentially mixed with the remaining alkenyl polyorganosiloxane, hydrosilylation inhibitor and organohydrogen polysiloxane. A platinum group metal catalyst is added at ≤35°C, and degassing is performed for 5-40 minutes at an absolute pressure of 0.5-15 kPa to obtain the interface sulfur barrier optical silicone composition for LED beads.
7. The application of the interface sulfur-resistant optical silicone composition for LED lamp beads according to any one of claims 1 to 5, characterized in that, It is applied to the preparation of transparent LED bead packages with silver-plated supports, so that the cured composition comes into contact with the silver-plated metal surface and the support cup, and continuously covers the adjacent interface between the silver-plated metal surface and the support cup.
8. The application of the interface sulfur-resistant optical silicone composition for LED lamp beads according to claim 7, characterized in that, The composition is applied to a silver-plated bracket in which an LED chip is mounted, such that the composition covers the LED chip and the interface between the silver-plated metal surface and the bracket cup. After application, let stand at 20~50℃ for 5~30 minutes, then pre-cur at 70~100℃ for 15~50 minutes, and finally post-cur at 120~155℃ for 30~120 minutes.
9. An LED light bead, comprising a bracket, an LED chip disposed within the bracket, and a transparent silicone encapsulation covering the LED chip, characterized in that, The bracket includes a silver-plated metal surface and a bracket cup formed of polyphthalamide, poly(1,4-cyclohexanediol) terephthalate, or epoxy molding compound; the transparent silicone encapsulation is formed by curing the interface sulfur-resistant optical silicone composition for LED beads according to any one of claims 1 to 5, and continuously covers the silver-plated metal surface and the adjacent interface between the silver-plated metal surface and the bracket cup.
Citation Information
Patent Citations
Transparent heat-protecting glass paint
CN102604449A
Alkoxysilyl group-containing azo compound and rubber composition using the same
US8741994B1